2019
DOI: 10.20546/ijcmas.2019.802.112
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition of Raw, Malted and Popped Finger Millet (Eleusine coracana) Varieties

Abstract: Finger millet commonly known as Ragi is a rich source of several nutrients. An investigation was undertaken to study the nutritional composition of raw, malted and popped finger millet varieties. Five varieties of finger millet namely GPU 66, GPU 67, GPU 71, MR 6 and PR 202 were investigated for their nutritional contents before and after processing such as malting and popping. The nutrients analysed for raw, malted and popped finger millet varieties were moisture, protein, fat, crude fibre, ash and total diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The growing environment may have an impact on the uptake, translocation, and accumulation of mineral elements [12]. Similar to the current study, variability in mineral contents among different nger millet genotypes was reported in previous studies [21,23,28,29]. One of the best ways to address severe malnutrition issues is through bioforti cation, which increases the density and availability of micronutrients [30].…”
Section: Principal Component Analysissupporting
confidence: 85%
“…The growing environment may have an impact on the uptake, translocation, and accumulation of mineral elements [12]. Similar to the current study, variability in mineral contents among different nger millet genotypes was reported in previous studies [21,23,28,29]. One of the best ways to address severe malnutrition issues is through bioforti cation, which increases the density and availability of micronutrients [30].…”
Section: Principal Component Analysissupporting
confidence: 85%
“…Low‐cost techniques for raw materials preparation can be tolerably blended into bread, noodles, or breakfast cereal formulation, without hampering the techno‐functional properties and sensory attributes from the preview of consumer's acceptability (Kotsiou et al, 2021). It is noteworthy that recent dry‐heat studies assessed in form of open pan, sand, and salt‐bed roasting on several cereal kernels such as corn, chia, sweet chestnut, sorghum, Kodo, finger millet, amaranth, parboiled chaul, plain and pigmented wheat, and so forth, stand out as fast, toxic‐free, eco‐friendly wholesome techniques for physical starch‐modification, with improved sensory features, techno‐functional structural and rheological properties (Cabrera‐Ramírez et al, 2021; Chauhan & Sarita., 2018; Dhua et al, 2021; Dutta et al, 2016; Hatamian et al, 2020; Hiremath & Geetha, 2019; Wani et al, 2017). To deactivate the post‐harvest enzyme activity of cereals susceptible to oxidative rancidity incurring short shelf life, roasting a simple household grain, convenient process that uses dry heat with peculiarity of utilizing moisture values below 20% for a short period of time (60–180 s) at higher temperature (115–350°C) is applied (Cabrera‐Ramírez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, finger millet is more suitable for drought-prone areas in semi-arid regions [1,2,3] and cultivated as a rainfed crop by >90% of finger millet area [4]. Additionally, finger millet has many dietary advantages with high calcium, iron, amino acids, fibre, and polyphenols [5,6,7,8,9]. Livestock also prefers finger millet fodder (haulm) because it contains more than 60% of nutrients in digestible form [10].…”
Section: Introductionmentioning
confidence: 99%